Improving Students Reading Comprehension Using Listen-Read-Discuss Strategy - Rifara; Mashuri; Dewi, Anjar Kusuma; Patmasari, Andi (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
The aim of this research is to determine whether the Listen-Read-Discuss (LRD) strategy can improve the reading comprehension of seventh-grade students at SMP Negeri 10 Palu. A quantitative approach was employed, using a pre-experimental design involving a single class—the experimental group. The population consisted of 65 seventh-grade students, from which a purposive sample of 32 students from class VII Ketapang was selected. Data were collected through a test comprising a pre-test and a post-test. The results show that the LRD strategy effectively enhanced students' reading comprehension, as evidenced by an increase in the average score from 56.33 (pre-test) to 87.44 (post-test), reflecting a 31.11-point improvement. These findings suggest that the LRD strategy can serve as an effective instructional approach for teaching descriptive texts and improving students' reading comprehension skills.